1980
DOI: 10.1056/nejm198005223022102
|View full text |Cite
|
Sign up to set email alerts
|

An Inherited Abnormality of Neutrophil Adhesion

Abstract: Neutrophils from a five-year-old boy with recurrent bacterial infections failed to spread on surfaces, leading to a severe defect in chemotaxis and a mild impairment in phagocytosis. Failure to spread was also seen in a fraction of the neutrophils from the patient's mother and sister, but cells from his father and brother were normal. Gel electrophoresis revealed that a protein with a molecular weight of 110,000 daltons (designated gp 110) present in the particulate fraction of normal neutrophils was absent fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
1

Year Published

1985
1985
2010
2010

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 268 publications
(47 citation statements)
references
References 29 publications
0
45
1
Order By: Relevance
“…PMN adherence is not only important in PMN margination to vascular endothelium but also provides anchoring of the cell for forward movement. Several children with a PMN membrane glycoprotein deficiency that prevents normal adherence have been described (34,35). These children have markedly decreased PMN chemokinesis and chemotaxis and recurrent bacterial and fungal infections.…”
Section: Discussionmentioning
confidence: 99%
“…PMN adherence is not only important in PMN margination to vascular endothelium but also provides anchoring of the cell for forward movement. Several children with a PMN membrane glycoprotein deficiency that prevents normal adherence have been described (34,35). These children have markedly decreased PMN chemokinesis and chemotaxis and recurrent bacterial and fungal infections.…”
Section: Discussionmentioning
confidence: 99%
“…Translocation of p47 PHOX from Cytosol to Plasma Membrane-Transfected lymphoblasts were treated for 15 min at 4°C with diisopropylfluorophosphate as described elsewhere (18). The cells were then washed, resuspended in phosphate-buffered saline (10 8 cells/ml), and incubated at 37°C for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…In addition it has been shown that both molecules act as adhesion molecules on granulocytes [7,23,24]. However, Mo-1 and LFA-1 have different a chains and are distributed on different cell types.…”
Section: Biological Properties Of Mo-1 and Lfa-1mentioning
confidence: 99%